Neolithic pastoralism in marginal environments during the Holocene Humid Period, northern Saudi Arabia. (2nd October 2018) - Scerri, Eleanor M.L.; Guagnin, Maria; Groucutt, Huw S.; Armitage, Simon J.; Parker, Luke E.; Drake, Nick; Louys, Julien; Breeze, Paul S.; Zahir, Muhammad; Alsharekh, Abdullah; Petraglia, Michael D.
Abstract : Abstract : The origins of agriculture in South-west Asia is a topic of continued archaeological debate. Of particular interest is how agricultural populations and practices spread inter-regionally. Was the Arabian Neolithic, for example, spread through the movement of pastoral groups, or did ideas perhaps develop independently? Here, the authors report on recent excavations at Alshabah, one of the first Neolithic sites discovered in Northern Arabia. The site's material culture, environmental context and chronology provide evidence suggesting that well-adapted, seasonally mobile, pastoralist groups played a key role in the Neolithisation of the Arabian Peninsula.